2022
DOI: 10.1002/cpt.2615
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors and Venous Thromboembolism: An Analysis of the WHO Pharmacovigilance Database

Abstract: Data on venous thromboembolic events (VTEs) in patients receiving immune checkpoint inhibitors (ICIs) are scarce and conflicting. This study investigated the risk of reporting VTEs associated with ICIs in comparison with all other anticancer drugs. The World Health Organization pharmacovigilance database (VigiBase), comprising >30 million individual case safety reports, was queried. All reports on patients with cancer, involving at least one anticancer drug as a suspect or interacting drug and registered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Given the observational nature of this study and the overall small number of CV events, we are not able to draw connections between whether the use of ICIs led to CV events like VTE and ischemia. Interestingly, through analysis of the World Health Organization pharmacovigilance database, Allouchery et al 18 found that ICIs did not correlate with higher reporting of VTEs compared with other anticancer drugs. In contrast, Drobni et al 19 showed that atherosclerotic cardiovascular events increased after ICI initiation as did atherosclerosis on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Given the observational nature of this study and the overall small number of CV events, we are not able to draw connections between whether the use of ICIs led to CV events like VTE and ischemia. Interestingly, through analysis of the World Health Organization pharmacovigilance database, Allouchery et al 18 found that ICIs did not correlate with higher reporting of VTEs compared with other anticancer drugs. In contrast, Drobni et al 19 showed that atherosclerotic cardiovascular events increased after ICI initiation as did atherosclerosis on imaging.…”
Section: Discussionmentioning
confidence: 99%